Implementation of New Technology in Service Industry: Are the Consumers Ready? - Mohamed, Muharis; Patwary , Ataul Karim (South Asian Journal of Social Sciences and Humanities, 2020)
Technological advancement has prioritized every aspect of human living, no exception in the  service industry. From consumers' perspectives, a question remained unsolved, how ready are  the consumers to adopt existing and upcoming technologies, specifically in service industry?  To explore that, this research attempted to figure out related factors that either directly or  indirectly influence consumers while adopting new technologies. This research provided a  detailed understanding of the consumers' experience in technology adoption, explores  consumer views of technologically advanced and linked service environments, and strengthens  this understanding by outlining how customer perceptions are affected by contextual variables  (objects, behaviors, actors, and artifacts). This research uses a holistic approach to consider  consumer experience in the context of intelligent energy services. Intelligent innovations have  significantly transformed the service environment, but consumer engagement with intelligent  systems remains scarce. In this report, intelligent services are defined, consumer behavior in  this new environment is well understood, and important consequences for management and  service science are addressed.
Keywords: New Technology; Service Industry; Technological Acceptance; Consumers